The effect of ejaculation time on varicose vein diameter and reflux level. (28th April 2021) - Kizilkan, Yalcin; Duran, Mesut Berkan; Senel, Samet; Yikilmaz, Taha Numan; Akbelen, Behcet; Toksoz, Serdar
Summary: The aim of this study was to investigate whether the time interval between ejaculation and scrotal Doppler ultrasonography affects the results of the varicose vein diameter and reflux time. Age, medication use, operation history, physical examination and semen analysis findings, varicose vein diameters and the presence of reflux and reflux time were evaluated prospectively in the patients older than 18 years of age who presented to the urology outpatient clinic with infertility and underwent scrotal Doppler ultrasonography and semen analysis. The time interval between the two scrotal Doppler ultrasonography for semen analysis was noted, the two results were compared. The patients were divided into four groups according to the time interval between ejaculation and scrotal Doppler ultrasonography. The study included 81 varicocele cases, with 57 left‐sided and 12 bilateral varicocele. The varicose vein diameters were significantly larger after ejaculation than before ejaculation ( p  < .001). Similarly, the reflux time after ejaculation in all patients was significantly higher in scrotal Doppler ultrasonography performed before and after ejaculation at rest and during Valsalva manoeuvre ( p  < .001). In conclusion, the results of the present study suggest that a waiting time of at least 90 min must be allowed between ejaculation and scrotal Doppler ultrasonography.